Effects of Site on Winter Wheat Quality 2002/2003 - Tóth, Árpád; Győri, Zoltán (Acta Agraria Debreceniensis, 2019)
The demand of modern societies for high food quality is evident. Thus, it is important for agriculture to produce row materials that are valuable for nutrition and have favourable characteristics for food processing. For this we need a knowledge about the factors which determine the quality of products. One of the main features of plant production is the “immobility”. This way the characteristics of the field influence the quality of the product, like example winter wheat, which is the main cereal in Hungary and Europe.The Concordia Co. has charged the Central Laboratory of Debrecen University, Agricultural Centre with laboratory testing of the 2002/2003 winter wheat crop. The samples consist of thirteen winter wheat varieties from six different sites under the same cultivating conditions. Therefore, the important wheat quality factors were analysed solely against site conditions with the use of Győri’s “Z” index, which contains these parameters.Soils were tested first. In this experiment excepting the negligible differences between the sites, there were no linear relations found between quality factors, productivity and soil features. The case is the same with the relation between precipitation, temperature and quality parameters. However, it must be noted that additional soil analyses are required to interpret the extreme results obtained from Karcag.The calculated Győri’s Z-index shows relative stability concerning certain varieties, although considerable deviation can be found in varieties related to the sites. According to these results, it can bestated that winter wheat quality was not linearly influenced by soil and weather in the 2002/2003 vegetation period. As the same cultivation technology was used in the experiment, the index was determined by genetic features. It must be noted that these findings are relevant only to this experiment.